Subglacial-discharge plumes drive widespread subsurface warming in northwest Greenland’s fjords - Cowton, Tom; Slater, Donald; Inall, Mark (Geophysical Research Letters, 2023)
This work was supported by the UK Natural Environment Research Council (Grants NE/W00531X/1 and NE/T011920/1). Greenland’s glacial fjords modulate the exchange between the ice sheet and ocean. Subglacial-discharge-driven plumes adjacent to glaciers may exert an important influence on fjord water properties, submarine glacier melting and the export of glacially-modified waters to the shelf. Here we use a numerical plume model in conjunction with observations from proximal to 14 glaciers in northwest Greenland to assess the impact of these plumes on near-glacier water properties. We find that in late summer, waters emanating from glacial plumes often make up > 50 % of the fjord water composition at intermediate depths. These plume waters are comprised largely of upwelled Atlantic Water, warming the near-glacier water profile and likely increasing submarine melting. Our findings demonstrate the key role played by plumes in driving water modification in Greenland’s fjords, and the potential for simple models to capture these impacts across a range of settings. Peer reviewed